Self-selection, socialization, and risk perception: an empirical study - Ursula Weisenfeld; Ingrid Ott (Kiel Institute for the World Economy (IfW), 2009)
We analyze students' knowledge and risk perception of four technologies. The aim is to find out whether there is a relationship between area of study (self-selection) and progress of study (socialization) on the one hand and risk perception of technologies regarding health, environment and society on the other. The four technology fields under study are renewable energies, genetic engineering, nanotechnology and information and communication technologies (ICT). Key results are: Irrespective of study area, study progress and gender, genetic engineering has the highest perceived risk and renewable energies has the lowest. This holds for all the risks studied (environmental, health, societal risks). For most risk perception variables, advanced students perceive lower risks than beginners, and students in a technical study area perceive lower risks than students in a non-technical area. Factor analyses show that common dimensions of risk are the technological areas and not the type of risk. Regression analyses show that the variables influencing perceived risks vary between the technological fields.
Keywords: O33; 330; Technologies; risk perception; self-selection; socialization; Technikbewertung; Risikopräferenz; Wahrnehmung; Studierende; Studienfach; Berufswahl; Sozialisation; Deutschland